Expression of Assumption of Sustainability in the Ideas Bronislovas Bitinas for Teaching and Learning Change - Kazlauskienė, Aušra (Pedagogika, 2016)
According to European Commission communiques (Opening up Education: Innovative teaching and learning for all through new Technologies and Open Educational Resources, 2013; Europe 2020, 2010; Taking stock of the Europe 2020 strategy for smart, sustainable and inclusive growth, 2014), scientists (Tilbury, 2011; Tilbury, & Mula, 2009; Pipere, Salite, & Veisson, 2015) works, there is emphasizing the key point of sustainability in education. Sustainable development few last decades remain that supporting category upon which is tried to analyse and understand the dynamics of difficult systems or procedures, estimate their problems of interactions, compatibility and other. One of the most relevant branches of development in education in National education strategy 2013–2022 (2013) is directed to quality of education. Its main strategic purpose – to turn Lithuanian education into sustainable basis for improving national welfare, for thrusting and independent person who responsibly and independently creates his, countries and worlds future. Until now the key and expression of sustainability is more emphasizing through global cultural characteristics. This article aims to emphasize multicultural characteristics, to individualize the expression of sustainability more in prof. B. Bitinas work contexts. Using thematic synthesis enhanced review method in B. Bitinas works it is emphasized those principles of sustainability which are considered as new paradigm which changes the view to learning and education phenomena: open integrality (open and integral teaching and learning environment: learning for everyone, everywhere, anytime, with any measures and with any help. That helps to ensure teaching and learning efficiency and helps to gain new abilities), succession and continuance (as condition of change), technological approach (creating ability to raise efficiency and justice), dialogue (as interaction, responsibility as assumption to create teaching and learning meanings in society of diversity).